PROBLEMATIKA PEMBEKUAN PERUSAHAAN PIALANG OLEH BADAN PENGAWAS PERDAGANGAN BERJANGKA KOMODITI - Anissa Sylviana, (2023)
Based on the Decree of the Head of Bappebti Number 01 of 2022 dated March 8, 2022, Bappebti suspended the business activities of PT Rifan Financindo Berjangka because it had violated the rules in carrying out business activities. Regulations related to commodity futures trading are regulated in Law No. 10 of 2011 concerning Commodity Futures Trading. This study uses a normative juridical research method, with a statutory approach (statue approach) and a case approach (case approach). The focus in this research is how to enforce the law against brokerage companies that violate operational activity rules in carrying out futures brokerage business activities and the responsibility of brokerage companies whose operational permits have been suspended by the Commodity Futures Trading Regulatory Agency for their customers. The purpose of this research is to find out law enforcement by the government against brokerage companies that violate the rules and responsibilities of brokerage companies to customers and employees as a result of the suspension. The results of this study resulted in law enforcement against brokerage companies that have violated the rules, namely receiving administrative sanctions in the form of freezing business activities based on PP No. 9 of 1999 concerning the Implementation of Commodity Futures Trading and the responsibility of brokerage companies to customers and employees by improving operational activities and preparing documents requesting the disbursement of freezing of business activities and continuing to guarantee the payment of employee wages according to the agreed time.